Current treatment of mantle cell lymphoma: results of a national survey and consensus meeting - Witzens-Harig, Mathias (Annals of hematology, 2012)
In most patients, mantle cell lymphoma (MCL) shows an aggressive clinical course with a continuous relapse pattern and a median survival of only 3-5 years. In the current study generation of the European MCL Network, the addition of high-dose Ara-C to R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone)-like regimen followed by myeloablative consolidation achieved a significant improvement of progression-free survival in younger patients. In elderly patients, rituximab maintenance led to a marked prolongation of remission duration. Emerging strategies include mammalian target of rapamycin (mTOR) inhibitors, proteasome inhibitors, immune modulatory drugs, Bruton’s tyrosine kinase inhibitors and others, all based on the dysregulated control of cell cycle machinery and impairment of several apoptotic pathways. Combination strategies are currently being investigated in numerous trials, but their introduction into clinical practice and current treatment algorithms remains a challenge. In the current survey, the application of the molecular targeted compounds were collected and evaluated by a representative national network of 14 haematological institutions. Optimised strategies are recommended for clinical routine. Future studies will apply individualised approaches according to the molecular risk profile of the patient.